(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Putintsev A. V. Problems applying pedagogical modeling in the process of professional training of future marketing specialists. In the article attention is accented on the problem of increase of competitiveness of graduating students of higher educational establishments, in particular future marketing specialists, theoretical basis of pedagogical modeling are investigated, types of pedagogical models, determination and classifìcatìon of pedagogical models are defined.